Spiritual reminiscence therapy for older people with loneliness, anxiety and depression living in a residential aged care facility, Malaysia: A qualitative approach - Syed Elias, Sharifah Munirah; Petriwskyj, Andrea; Scott, Theresa; Neville, Christine (Blackwell Publishing Ltd, 2019)
Objective: To explore how older people with loneliness, anxiety and depression experience a spiritual reminiscence therapy (SRT) program and to explore its acceptability within the Malaysian population. Methods: Unstructured observations and a focus-group discussion were carried out with 18 participants involved in a six-week SRT program in a residential care facility in Kuala Lumpur. Results: Analysis revealed four themes: (i) Enthusiastic participation; (ii) Connections across boundaries; (iii) Expressing and reflecting; and (iv) Successful use of triggers. Conclusions: The findings suggest that the process of reminiscence, on which the program was based, was enjoyable for the participants and created opportunities to form connections with other members of the group. The use of relevant triggers in the SRT program that related to Malaysian cultures, ethnicities and religions was helpful to engage the participants and was acceptable across the different religions and ethnicities.